COMPARISON BETWEEN THE TYPES OF HYDROPONICS AND REGULAR CULTIVATION IN THE SOIL AND THEIR IMPACT ON THE GROWTH OF THE LETTUCE CROP - Ali Asim Mutar Arak; Zainab Thamer obeis Hussein; Baraa Amer Hamid Qadir; Haider Abbas Shadhan Abd; Mohammed Abbas Hamza Abd alhasan; Riyam Kareem Tlayyip Hamoud (Journal of Medical Genetics and Clinical Biology, 2024)
This study aimed compare the morphological properties of lettuce growth in different model of cultivation (soil, cork and water pipes). Samples of lettuce plants were cultivated in three models of cultivation. The first model was regular cultivation in soil, the second model was agriculture using water pipes and the third model was hydroponic using cork. After two months, the properties of each sample, including total length of plant, length of stem to end of leaf, length of root, length of leaves and number of roots. According to the result in this study, length of total plant, root, leaves and stem to end as well as number of leaves and roots were significantly greater in water pipes than in hydroponic with cork and soil, respectively..